The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/hsr2.1222
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalized COVID‐19 patients with diabetes have an increased risk for pneumonia, intensive care unit requirement, intubation, and death: A cross‐sectional cohort study in Mexico in 2020

Abstract: Background: Diabetes mellitus is a chronic health condition that has been linked with an increased risk of severe illness and mortality from COVID-19. In Mexico, the impact of diabetes on COVID-19 outcomes in hospitalized patients has not been fully quantified. Understanding the increased risk posed by diabetes in this patient population can help healthcare providers better allocate resources and improve patient outcomes. Objective: The objective of this study was to quantify the extent outcomes (pneumonia, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Community-Acquired Pneumonia (CAP) is an acute lung infection that causes 1.5 million hospitalizations in the United States each year [ 13 ]. A Recent study showed that the hospitalized COVID-19 patients with diabetes have an increased risk for pneumonia, intensive care unit requirement, intubation, and death [ 14 ]. As the COVID pandemic continues to evolve, health systems could see subsequent waves with large numbers of patients admitted to the inpatient setting with COVID-19 pneumonia, consuming valuable resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Community-Acquired Pneumonia (CAP) is an acute lung infection that causes 1.5 million hospitalizations in the United States each year [ 13 ]. A Recent study showed that the hospitalized COVID-19 patients with diabetes have an increased risk for pneumonia, intensive care unit requirement, intubation, and death [ 14 ]. As the COVID pandemic continues to evolve, health systems could see subsequent waves with large numbers of patients admitted to the inpatient setting with COVID-19 pneumonia, consuming valuable resources.…”
Section: Discussionmentioning
confidence: 99%
“…After adjusting for the 11 risk factors, we identified previously [ 3 ], the AUC’s of the PSI-17 and PSI-20 models both increased to above 0.85. The PSI is not comprehensive and other model features could be added, such as diabetes, which is a known risk factor for poor outcomes in COVID-19 [ 14 ] and is not one of the listed co-morbidities in PSI ( S1 Table ). Pneumonia predictive scores have been studied in COVID-19 and PSI was shown as one of the better performing scores for 30-day COVID mortality along with CURB-65, and covid specific scores: 4C and COVID GRAM among 11 different scores for mortality assessment [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Khan et al 12 provided a comprehensive overview of the global epidemiology of type 2 diabetes, emphasizing its increasing prevalence and the urgent need for effective management strategies. This perspective is particularly relevant in the context of recent health crises, such as the COVID‐19 pandemic, where Huang et al 13 identified a significantly increased risk of severe outcomes and mortality among hospitalized patients with diabetes in Mexico. These findings emphasize the critical need for effective diabetes management and preventive strategies.…”
Section: Introductionmentioning
confidence: 99%
“…To address these gaps and limitations, the present study focuses on the Mexican population and seeks to investigate the relationship between diabetes and COVID‐19 mortality. Patients that contract COVID‐19 have a range of symptoms ranging from asymptomatic to death 27 . Previous studies have looked at mortality in COVID‐19, but have not looked at the specific subset of individuals in Mexico with comorbid diabetes with the level of statistical analyses utilizing both Cox proportional hazards and restricted mean survival time 11,28,29 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients that contract COVID-19 have a range of symptoms ranging from asymptomatic to death. 27 Previous studies have looked at mortality in COVID-19, but have not looked at the specific subset of individuals in Mexico with comorbid diabetes with the level of statistical analyses utilizing both Cox proportional hazards and restricted mean survival time. 11,28,29…”
Section: Introductionmentioning
confidence: 99%